Fc‐binding proteins enhance autoantibody‐induced BP180 depletion in pemphigoid. Issue 3 (16th January 2019) - Iwata, Hiroaki; Kamaguchi, Mayumi; Ujiie, Hideyuki; Ujiie, Inkin; Natsuga, Ken; Nishie, Wataru; Shimizu, Hiroshi
Abstract: Immunoglobulins (Igs) consist of two antigen‐binding regions (Fab) and one constant region (Fc). Protein A and protein G are bacterial proteins used for the purification of IgG by virtue of their high affinities for the Fc fragment. Rheumatoid factors are autoantibodies against IgG Fc fragments, which are present in the body under physiological conditions. Little is known about the influence of Fc‐binding proteins on the pathogenicity of antibody‐induced autoimmune diseases. Pemphigoid diseases are a group of autoimmune subepidermal blistering disorders that includes bullous pemphigoid and mucous membrane pemphigoid. IgGs targeting the non‐collagenous NC16A domain of the 180‐kDa bullous pemphigoid antigen (BP180) are known to induce skin fragility in mice and the depletion of BP180 in keratinocytes. In this study, mAb against NC16A in combination with Fc‐binding proteins was found to enhance BP180 depletion. Although mAb against the C‐terminus of BP180 does not show pathogenicity in vivo or in vitro, mAb treatment with Fc‐binding proteins clearly induced skin fragility in mice and BP180 depletion in keratinocytes. Anti‐BP180 mAbs and Fc‐binding proteins were colocalized in the cytoplasm and at the basement membrane zone. Cell adhesion strengths were decreased in parallel with BP180 amounts. Clinically, bullous pemphigoid patients had higher rheumatoid factor titers than controls. Anti‐BP180 mAb in combination with high‐titer rheumatoid factor serum was found to enhance BP180 depletion. Furthermore, saliva from mucous membrane pemphigoid patients contained larger quantities of bacteria and Fc‐binding proteins than controls. Our results suggest that Fc‐binding proteins (rheumatoid factor or protein G) may enhance the pathogenicity of autoantibodies in pemphigoid diseases. Copyright © 2018 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.